2006
DOI: 10.1143/jpsjs.75s.149
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Uranium(III) Triflate in Tetrahydrofuran by Reduction of U(OTf)4with Zinc amalgam

Abstract: In order to develop an alternative preparation method of uranium(III) precursors soluble in aprotic organic solvent used for the preparation of uranium(III) compounds, U(IV) triflate, U(OTf) 4, in tetrahydrofuran (THF) was reduced to produce uranium(III) triflate. U(OTf)4 in THF was completely reduced by large excess of zinc within 25 minutes. Energies and molar coefficients of the absorption bands of U(III) triflate are close to those of U(III) in 1M HCl aqueous solution especially in the range of (9 ∼ 14)×10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…It has been shown that under inert air conditions aqueous solutions of U 3+ and Np 3+ can be produced electrochemically or by zinc amalgam . This technique was used to produce the hydrated trihalides, formate, a variety of sulfate complexes, and most recently the aquo triflate series. The U 3+ sulfate complexes have the general formula AU(SO 4 ) 2 ·XH 2 O (A = NH 4 + , Na + , K + , Rb + , Cs + ) or U 2 (SO 4 ) 3 ·8H 2 O. These were synthesized under low-temperature inert-atmosphere conditions producing marginally air-stable products, and while the reflectance spectra and magnetic susceptibilities were reported, the only crystal structure published from all of these sulfate compounds is that of NH 4 U(SO 4 ) 2 ·4H 2 O .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that under inert air conditions aqueous solutions of U 3+ and Np 3+ can be produced electrochemically or by zinc amalgam . This technique was used to produce the hydrated trihalides, formate, a variety of sulfate complexes, and most recently the aquo triflate series. The U 3+ sulfate complexes have the general formula AU(SO 4 ) 2 ·XH 2 O (A = NH 4 + , Na + , K + , Rb + , Cs + ) or U 2 (SO 4 ) 3 ·8H 2 O. These were synthesized under low-temperature inert-atmosphere conditions producing marginally air-stable products, and while the reflectance spectra and magnetic susceptibilities were reported, the only crystal structure published from all of these sulfate compounds is that of NH 4 U(SO 4 ) 2 ·4H 2 O .…”
Section: Introductionmentioning
confidence: 99%